Guidelines on the Nagoya Protocol for CGIAR Research Centers - CGIAR System Organization; Halewood, Michael; López Noriega, Isabel; Tobin, Brendan; Moore, Gerald (CGIAR System Organization, 2018)
These guidelines are meant to help the CGIAR Centers understand which areas of their plant genetic resources-related activities could be affected by the Nagoya Protocol, and what their options are in terms of how they can comply with the legal obligations. The guidelines address situations where countries have national laws in place implementing the Nagoya Protocol as well as situations where the countries concerned have ratified or acceded to the Nagoya Protocol but do not yet have national laws and systems in place to implement it.